Aesthetic sensitivity: relationship with openness to experience and agreeableness, health-related quality of life and adaptive coping strategies in people with high sensory processing sensitivity - Chacón, Antonio; Borda-Mas, Mercedes; Rivera, Francisco; Pérez-Chacón, Manuela; Avargues-Navarro, María Luisa (Frontiers in Psychology, 2024)
Aesthetic sensitivity in people with high sensory processing sensitivity (SPS) reflects the positive perception of life, especially aspects related to the arts and nature. This study is focused on the analysis of the effect of aesthetic sensitivity in relation to indicators of health-related quality of life (general health, mental health and emotional role), the personality traits openness to experience and agreeableness, and coping strategies in people with SPS. The adult participants (N=10520, mean age=33.61) completed the Spanish versions of the High Sensitivity Person Scale (HSPS-S), Short Form Health Survey (SF-36), NEO Five Factor Inventory (NEO-FFI) and Coping Strategies Inventory (CSI). It was observed that people with high aesthetic sensitivity presented greater openness and agreeableness, tended to use adaptive coping strategies and showed a slightly poorer functioning in different areas of daily living. Moreover, health-related quality of life, mental health and adaptive coping strategies occupied central positions in the correlations between variables, with a positive impact between mental health and adaptive coping strategies with openness and agreeableness. Lastly, the level of aesthetic sensitivity did not play a moderator role, and it exerted no differential influence on its relationship with the analysed variables. Now, it has been found that This is a provisional file, not the final typeset article people with high levels of aesthetic sensitivity cope more adequately, which would cushion the effect that high SPS can have on mental health, specifically on anxious and depressive symptoms. It is concluded that these findings are relevant and useful for future propositions of prevention and clinical intervention, as well as for counselling in the psychoeducational, labour and family scopes, among others.